Odpowiedzi

Najlepsza Odpowiedź!
2010-02-24T14:16:56+01:00
A) a+(a-b)=a+a-b=2a-b
b) 2x-(x+4)=2x-x-4=x-4
c) 7-(-x+6)=7+x-6=x+1
d) -(x+4)+(x-5)=-x-4+x-5=-9
e) 1-(t+p)-(t-2)=1-t-p-t+2=-2t-p+3
f) -(-y+2)+(-2y-4)=y-2-2y-4=y-6
19 4 19
2010-02-24T14:17:58+01:00
Wykonaj działania:
a) a+(a-b) = a + a - b = 2a - b
b) 2x-(x+4) = 2x-x-4 = x-4
c) 7-(-x+6) = 7+x-6 = 1+x
d) -(x+4)+(x-5) = -x-4+x-5 = -9
e) 1-(t+p)-(t-2) = 1-t-p-t+2 = 3-2t -p
f) -(-y+2)+(-2Y-4) = y-2-2y-4 = -6-y

Czy tak jest dobrze :
a) a+a-b=2a-b
b) 2x-x-4=x-4
c) 7+x-6=x+1
d) -x-4+x-5=-9
e) 1-t-p-t+2=-2t-p+3
f) y-2-2y-4=y-6 źle, masz y-2y czyli będzie -y
10 3 10
2010-02-24T14:21:05+01:00
A)a+a-b=2a-b
b)2x-x-4=x-4
c)7+x-6=x+1
d)-x-4+x-5=-9
e)1-t-p-t-2=-2t-p+3
f)y-2-2y-4=-y-6

w ostatnim pomieszane znaki
5 4 5